Development of Interactive Videos with Transportation Stories for PAUD - Utami, Laksmita Wahyu Chandra; Syafdaningsih, Syafdaningsih (THUFULA, 2022)
This study aims to develop a valid and practical interactive video media product for children’s stories with the theme of transportation. This research development method was combined with the ADDIE model and Tessmer’s formative evaluation. The first data collection technique used observation to assess the child’s behavior and then used a walkthrough to see the value of the validity of a product. The object of this research was the Interactive Video of Children’s Stories with the theme of transportation which went through a one-to-one trial stage (3 children) and small group (9 children), with the conclusion that the Interactive Video of children’s stories on the transportation theme was categorized as valid and practical. Validity was reflected in the results of the validator’s assessment, where the interactive video of students had been revised according to the validator’s suggestions and comments. Practically it was illustrated from the results of the trial, where all students can use interactive video stories with the theme of transportation that students can use well. Based on the results of the interactive video analysis, the story of the transportation developed theme has the appropriateness of learning for children and the suitability of the needs and development of children aged 5-6 years. In addition, it is in accordance with the observation assessment indicators, namely enthusiasm in using media. From this research, there is a novelty in using interactive video media with the theme of transportation which was made into an interesting story. It contributes to the world of early childhood education in the form of additional types of interactive learning media.